Safeguarding the Child’s Best Interests in Judicial Proceedings Through Digital Technology - Drnovšek, Katja (Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges, 2025)
Although appearing in court can cause significant psychological distress to children, especially when involved in criminal proceedings or family disputes, their participation in judicial proceedings is sometimes unavoidable. While children's procedural rights are rarely the main issue in proceedings before the ECtHR, its case law has nonetheless established certain standards concerning the need for child-friendly approaches. However, safeguarding children's rights to effective participation and to be heard while simultaneously protecting them from secondary victimisation remains challenging. With the development of technology and the digitalisation of judicial systems, new approaches and opportunities continue to emerge. Remote hearings and various digital tools hold great potential to make judicial proceedings less intimidating and traumatic when implemented with proper safeguards. The paper analyses relevant ECtHR case law, the psychological aspects of remote hearings, and some examples of Slovenian good practices concerning using digital tools in judicial proceedings involving children.